Expert System of Initial Anamnesis Process of Menstrual Disorders Using Certainty Factor Method. - Gina Giftia, Azmiana Delilah; Slamet, Cepy; Diena Rauda, Ramdania; Ulfiah, Ulfiah; Amalia, Mahmudah (2020)
Anamnesis is a preliminary examination to obtain information about the patient's disease. This process is carried out by the doctor as part of the initial diagnosis of the patient's condition. The purpose of this research is to assist the history process in eliminating the diagnosis of possible diseases from experts by adopting their knowledge into the expert system. The method used in this study is the Certainty Factor method. Fifty test data collected to test this approach. The test results showed 44 data following expert opinion and obtained an accuracy rate of 88%. These results indicate that the expert system is suitable for the early history of menstrual disorders